Hemorrhagic and ischemic complications of percutaneous transvalvular microaxial flow pump. (3rd May 2023) - Davila, E; Galan, D; Puerto, E; Vicent, L; Bruna, V; Dominguez, L; Durante, A; Otero, M; Guisasola, M; Penaloza, E; Jimenez, A; Martin, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Percutaneous Transvalvular Microaxial Flow Pump for Mechanical Circulatory Support (p-MCS) is increasingly used for treating cardiogenic shock (CS). However, it associates complications due to the need for a peripheral access and anticoagulation. Purpose: We aim to describe the bleeding and ischemic complications derived from p-MCS support and their possible causes. Methods: Analytical and observational study of 31 consecutive patients (pts) admitted for CS to our Acute Cardiovascular Care Unit who were assisted by p-MCS from March 2020 to September 2022. We analyze demographic and other variables with the use of conventional statistic. Results: The registry included 31 pts, 77, 4% were males and the mean age was 56, 5 years. The causes of CS were: 77, 4 % acute myocardial infarct (AMI), 6, 5 % arrhythmic storm, 12, 9% acute heart failure and 3, 2% mechanical complication of AMI. 21 were supported only by p-MCS (67, 7%), 9 by p-MCS and Venoarterial Extracorporeal Membrane Oxygenation (29%) and 1 by p-MCS for right and left ventricle simultaneously (3.2%). According to Society for Cardiovascular Angiography and Interventions (SCAI) classification, 6, 6% of pts were in stage B, 20% in C, 46, 7% in D and 26, 7% in E. The median support duration was 4 days. The mortality during support was 35% (11 pts) and at day 30, 42% (13 pts). 19, 3% presented ischemia of the limb where the p-MCS was inserted. 1 case was mild and 5 were major and required surgery (two compartimental syndromes due to muscular necrosis included). Women presented higher rates of ischemia (57, 1 vs 8, 4%, p=0.005) and trend to be more severe (100% of the cases were major vs 50% in men, p=0, 105). The pts who developed ischemia were older (62, 1 vs 55, 1 years, p=0.034). 40% of pts presented systemic bleeding: 2 (6, 7%) were fatal, 6 (20%) major (defined by the drop of 2 points of hemoglobin, the need for 10 ml/kg blood transfusion or retroperitoneal, pulmonary or surgery-required hemorrhages) and 4 (13, 3%) mild. The median of length support was 9 days in pts with systemic bleeding versus 3 days in pts without (p=0.016). Local (pericannula) bleeding appeared in 46, 7% of the pts, resulting major (dressing change every 4 hours) in 8 (26, 7%) and mild in 6 (20%). Regarding systemic ischemic events, 5 strokes (16.1%) were reported, without diferences between groups for the analyzed variables. Conclusions: p-MCS is effective at the management of CS with a mortality at 30 days of 42%, which is acceptable considering the pathology severity. However, it implies risk of ischemic and hemorrhagic complications. In our registry, 46.7% of the pts presented local bleeding, 40% systemic bleeding, 19, 3% limb ischemia and 16, 3% stroke. Female sex and older age seem to be risk factors for developing ischemia, as well as longer duration of support for systemic bleeding. More studies are needed to describe the pts profile who are more exposed to these complications and how to avoid them. Description of initial characteristics Complications incidence chart